(untitled) (Nóema, 2014)
The purpose of this note is to discuss some aspects of Prof. Smith’s paper about Virgil and the ambiguity. The note is divided into three parts: a) a discussion about the ambiguity of the empirical things in Plato; b) a reconsideration of Heraclitus’ fragment 26 DK, in the light of some observation by H.G. Gadamer; c) a short comparison between Virgil’s Polydorus and Dante’s Pier Delle Vigne about the uncanny nature of their otherworldly transfiguration.